Neuropati Optik Traumatik: Gambaran 13 Kasus Berdasarkan Radiologi dan Awitan Terapi Kortikosteroid di Rumah Sakit Cipto Mangunkusumo - Made Paramita Wijayati; Syntia Nusanti; M. Sidik (Majalah Oftalmologi Indonesia, 2021)
Introduction and Objection: Traumatic Optic Neuropathy is a rare and potentially vision-threatening condition caused by ocular or head trauma. The optic nerve axons may be damaged either directly or indirectly. The management of traumatic optic neuropathy could be observed, giving steroids or decompression. At center which optic nerve decompression is not routinely performed, high dose steroid is preferred for traumatic optic neuropathy patients. The study aims to analyze characteristics (mean age and gender, onset trauma, most symptom, visual acuity, consensual reflex as a sign), radiology feature, and onset corticosteroid therapy on patient traumatic optic neuropathy. Methods: This study was a descriptive observational case series which data retrospectively analysis from medical record. Result: From 13 cases most common gender affected were males (76,9%). The mean age group 32.85±14.67 years old with blurry vision and bleeding are the most common symptom, the onset of trauma below 24 hours (76.9%), the initial visual acuity is no light perception and hand movement with a negative consensual reflex (76.9%). Visual acuity improves with initial corticosteroid therapy below 24 hours are 7 cases and more than 24 hours are 2 cases. From 9 cases with visual acuity improvement, there are 4 cases with orbital fracture and 5 cases without orbital fracture. Conclusion: Visual improvement in our cases happened more on initial corticosteroid therapy more than 24 hours and no orbital fracture.